Roles of the Skp2/p27 axis in the progression of chronic nephropathy - Suzuki, Sayuri (Springer Basel, 2012)
S-phase kinase-associated protein 2 (Skp2) is an F-box protein component of the Skp/Cullin/F-box-type E3 ubiquitin ligase that targets several cell cycle regulatory proteins for degradation through the ubiquitin-dependent pathway. Skp2-mediated degradation of p27, a cyclin-dependent kinase inhibitor, is involved in cell cycle regulation. Tubular epithelial cell proliferation is a characteristic feature of renal damage that is apparent in the early stages of nephropathy. The p27 level is associated with the progression of renal injury, and increased Skp2 expression in progressive nephropathy is implicated in decreases of p27 expression. In Skp2(−/−) mice, renal damage caused by unilateral ureteral obstruction (UUO) was ameliorated by p27 accumulation, mainly in tubular epithelial cells. However, the amelioration of UUO-induced renal injury in Skp2(−/−) mice was prevented by p27 deficiency in Skp2(−/−)/p27(−/−) mice. These results suggest that the Skp2-mediated reduction in p27 is a pathogenic activity that occurs during the progression of nephropathy. Here, we discuss the roles of the Skp2/p27 axis and/or related signaling pathways/components in the progression of chronic nephropathy.